USING PROBLEM-BASED LEARNING TO TEACH SOFTWARE MODELING IN INFORMATION TECHNOLOGY COLLEGES IN INDONESIA - Bahar, Bahar; Wibawa, Basuki; Situmorang, Robinson (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
The Direct-Instruction model which is still widely used in the learning of software modeling in higher education places more emphasis on classroom interactions initiated by the teacher. Generally, it only involves a small portion of student-to-student interaction. The direct learning systems that depend on the reflection ability of instructors only provide few opportunities for students to be actively involved in the learning process. Thus, it is different from software modeling which emphasizes Student-Centered Learning. Consequently, learning becomes ineffective and students cannot reach the minimum competency standard stated in the learning design. This paper proposes a Problem-Based Learning model that is integrated in software modeling learning at three segments: Curriculum segment, emphasizing the use of problems as the starting point of student learning; group segment, emphasizing collaboration systems (group discussion-based-learning); and student segment, stressing the Student-Directed Learning (SDL) system. The effectiveness test results show that the application of the PBL model in 3 segments (Curriculum, Individual, Group) in the learning design of Software Modeling, is effective in increasing the level of student mastery of a particular topic.